Model Selection for the Preclinical Development of New Drug–Radiotherapy Combinations. Issue 11 (November 2021) - Singh, J.; Hatcher, S.; Ku, A.A.; Ding, Z.; Feng, F.Y.; Sharma, R.A.; Pfister, S.X.
Abstract: Radiotherapy plays an essential role in the treatment of more than half of all patients with cancer. In recent decades, advances in devices that deliver radiation and the development of treatment planning software have helped radiotherapy attain precise tumour targeting with minimal toxicity to surrounding tissues. Simultaneously, as more targeted drug therapies are being brought into the market, there has been significant interest in improving cure rates for cancer by adding drugs to radiotherapy to widen the therapeutic window, the difference between normal tissue toxicity and treatment efficacy. The development of new combination therapies will require judicious adaptation of preclinical models that are routinely used for traditional drug discovery. Here we highlight the strengths and weaknesses of each of these preclinical models and discuss how they can be used optimally to identify new and clinically beneficial drug–radiotherapy combinations.